Al-Qur’an dan Surah: Meningkatkan Kemampuan Menghafal Surah An-Nas pada Siswa Sekolah Dasar - Susriwati, Susriwati (Indonesian Journal of Research in Islamic Studies, 2024)
Each student has a difference in the ability to memorize and remember surah An-Nas. Each student can improve the ability to memorize by paying attention to better situations and conditions and paying attention to the right method to quickly memorize short letters. The purpose of this study was to determine the improvement of students' ability to memorize surah An-Nas at SDN 03 Ipuh. This type of research is Classroom Action Research (PTK). This research was conducted in 2023, the research location was at State Elementary School 03 Ipuh, Mukomuko Regency. The research subjects were class V students totaling 25. Data collection using observation, interviews and tests. Data analysis uses three steps, namely (1) data reduction; (2) data presentation; (3) conclusion drawing / data verification. The research stages include 4 steps, namely planning, implementation, observation and reflection. The results of the study revealed that the level of students' ability to memorize surah An-Nas increased after being given action, giving action on classroom learning through cycles I, II and III showed that students' ability to memorize surah An-Nas increased after being given action.